Bone Mineral Density and Fracture Risk in Obese Older Adults 12 Months After Completion of a 6-Month Higher Protein Diet and Exercise Intervention. (29th May 2020) - Starr, Kathryn Porter; Borack, Michael; Lyles, Kenneth; Miller, Marshall; Rincker, Jamie; McDonald, Shelley; Bales, Connie
Abstract: Objectives: Weight loss interventions for older adults often reduce bone mineral density (BMD), increasing risk of subsequent detrimental outcomes. This study explored the long-term impact of a higher protein diet plus exercise versus a diet plus exercise control treatment on body weight, bone mineral density at 3 sites, and fracture risk. Methods: Obese (BMI 34.3 ± 4.7 kg/m 2 ) older adults ( n  = 55; age = 70.0 ± 6.1 yrs) with Short Physical Performance Battery (SPPB) score = 9.2 ± 1.4 (out of 12) who completed a 6-month weight loss plus exercise trial were invited to return for assessment 12 months later. The original randomization was to either 0.8 g protein/kg body weight (Control) or 1.2 g protein/kg body weight, predominantly dairy (Protein). The 18-month assessment included BMD by DEXA (Hologic, Horizon model A) for femoral neck (FN), total hip (TH), and spine (lumbar vertebrae 1–4; LS), as well body weight and secondary outcomes for Fracture Risk Assessment Tool (FRAX). Results: A total of 38 (69.1%) study completers were assessed at 18 mo. Body weight was lower than baseline for both Control and Protein ( P < 0.01), with Control (−4.8%) trending towards better maintenance of weight loss vs Protein (−2.3%) ( P  = 0.06). BMD at 18 mo. was not different from baseline in both Control and Protein for LS (0.01 ± 0.05 g/cm 2 and −0.0002 ± 0.05 g/cm 2 ; P  = 0.512), FN (−0.01 ± 0.07 g/cm 2 and −.009 ± 0.04 g/cm 2 ; P  = 0.814) and TH (−0.012 ± 0.03 g/cm 2 and −.008 ± 0.033 g/cm 2 ; P  = 0.685). Change in BMD at 18 mo. did not differ by group at any site; the previously reported Protein group increase in LS at 6 mo. was not sustained. For individual fracture risk, between 0 and 18 mo., 6 improved (5 osteopenia to normal, 1 osteoporosis to osteopenia) and 1 worsened (normal to osteopenia but FRAX score below total and hip fracture thresholds). Conclusions: The finding that obese older adults can maintain a lower body weight for 12 months without a decline in BMD and no increase in fracture risk amplifies our previous findings of legacy benefits of a short term obesity intervention for older adults. Further study is needed to determine if the protein benefit to LS is sustained if the higher protein intake is continued long term. Funding Sources: This study was funded by the National Dairy Council and the US Department of Veterans Affairs Rehabilitation Research and Development Program.